Penguatan Kompetensi Tutor PKBM melalui Training of Trainers Pengembangan Modul Pembelajaran Literasi Sains dan Bahasa Berbasis Etnosains Kearifan Lokal Klaten - Dwi Bambang Putut Setiyadi; Sukini Sukini; Maria Melani Ika Susanti (Jurnal Pengabdian Kepada Masyarakat, 2026)
Science and language literacy remain challenges in non-formal education, as learning often emphasizes memorization and underutilizes local contexts as learning resources. This community service program aimed to strengthen the competence of Community Learning Center (PKBM) tutors in developing science and language literacy modules based on the ethnoscience and local wisdom of Klaten. The program employed a Training of Trainers (ToT) approach involving training sessions, module development workshops, and mentoring. Participants consisted of 20 tutors from three PKBM in Klaten Regency. Competence was evaluated through pretest and posttest questionnaires covering literacy understanding, pedagogical competence, module development, and learning implementation. Results indicated a 24,61%. increase in tutor competence, with the average score rising from 63,31 to 87,92. The program effectively enhanced tutors’ capacity to design contextual learning grounded in ethnoscience and local wisdom.